Microbial Metabolites: Critical Regulators in NAFLD - Dai, Xin; Hou, Huiqin; Zhang, Wanru; Liu, Tianyu; Li, Yun; Wang, Sinan; Wang, Bangmao; Cao, Hailong (Frontiers in Microbiology, 2020)
Non-alcoholic fatty liver disease (NAFLD) is the most common form of chronic liver disease throughout the world. The relationship between gut microbiota and NAFLD has been extensively investigated. The gut microbiota is involved in the regulation of NAFLD by participating in the fermentation of indigestible food, interacting with the intestinal mucosal immune system, and influencing the intestinal barrier function, leading to signaling alteration. Meanwhile, the microbial metabolites not only affect the signal transduction pathway in the gut but also reach the liver far away from gut. In this review, we focus on the effects of certain key microbial metabolites such as short-chain fatty acids, trimethylamine-N-oxide, bile acids, and endogenous ethanol and indole in NAFLD, and also summarize several potential therapies targeting the gut–liver axis and modulation of gut microbiota metabolites including antibiotics, prebiotics, probiotics, bile acid regulation, and fecal microbiota transplantation. Understanding the complex interactions between microbial metabolites and NAFLD may provide crucial insight into the pathogenesis and treatment of NAFLD.